2018
DOI: 10.1051/matecconf/201820404007
|View full text |Cite
|
Sign up to set email alerts
|

Development of an open-loop ground source cooling system for space air conditioning system in hot climate like Indonesia

Abstract: Ground source cooling system (GSCS) is promising technology to serve cooling demands of buildings. This study presents a development of an open-loop GSCS for space air conditioning at Hasanuddin University Gowa campus. Experimental study was carried-out by pumping water from well of 57 m depth and flowing the water over a heat exchanger to cool refrigerant of air conditioning (AC) unit. The performance of AC unit was investigated under actual operation with various water flowrates. The temperatures of inlet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moreover, 'touchy' means to feel grief or unhappiness, or be in a distress mood [51]. Indonesia has two seasons, the dry season and the rainy season [52], and the dry season is often characterized by a hot climate [53]. During this season, most women are affected by the extremely hot weather, which eventually affects their psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 'touchy' means to feel grief or unhappiness, or be in a distress mood [51]. Indonesia has two seasons, the dry season and the rainy season [52], and the dry season is often characterized by a hot climate [53]. During this season, most women are affected by the extremely hot weather, which eventually affects their psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a GSHP is able to save 30% of required space cooling energy compared to a conventional air conditioner. Miyara, Ishikawa [22] developed and investigated the performance of a GSHP system for space cooling in Indonesia. The results found that the proposed geothermal-based cooling system is appropriate for cooling buildings in a hot climate like Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The development of water heating technology to produce hot water has been studied in the Renewable Energy Laboratory of Hasanuddin University. The possibility of producing hot water using a hybrid system with a ground source cooling system has been investigated [12][13][14]. The use of a V-shape absorber plate shown an increase in the absorptivity of the absorber plate [15] and integrated with various PCM materials such as paraffin wax [16].…”
Section: Introductionmentioning
confidence: 99%